Improvement in Tuberculosis Outcomes With a Combined Medical and Social Approach - Mazza-Stalder, Jesica; Chevallier, Emilie; Opota, Onya; Carreira, Ana; Jaton, Katia; Masserey, Eric; Zellweger, Jean Pierre; Nicod, Laurent Pierre (Frontiers in Medicine, 2019)
Setting: Studies performed locally in Switzerland in the late eighties reported unsatisfactory treatment outcomes. Better outcomes were observed since the introduction of directly observed therapy (DOT) in the late nineties and improvement in social support in recent years. Design: retrospective study of treatment outcomes for all tuberculosis (TB) patients notified in Vaud County (VD), Switzerland, between, 1st of January 2010 and 31st of December of 2014. Results: 375 patients were notified in VD during the study period. The global outcome was successful in 90.1% of patients (338/375). In 183 culture and PCR positive pulmonary TB, the documented cure rate was 57.9% (106/183), and the treatment completion was 59/183 (32.2%), i.e., a treatment success of 90.2%. DOT was applied globally in 234/375 (62.4%) and in 64/67 of the asylum seekers (AS) (95.5%) followed at the dispensary. Treatment outcomes were successful in 60/67 (89.6%) AS. Discussion: Improvements in tuberculosis outcomes resulted not only from the introduction of DOT in VD in the nineties but also from a change in the management, with increased attention to the social problems faced by the migrants. Conclusion: A combined medical and social approach of TB care in VD improved treatment outcomes.